THREATS ASSESSMENT OF FINANCIAL AND ECONOMIC SECURITY OF HOUSING AND PUBLIC UTILITIES BASED ANALYTIC HIERARCHY PROCESS - Мізік, Ю. І. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2014)
The paper is devoted to the use of Analytic Hierarchy Process for assessing the significance of classes and types of threats to the financial and economic security of housing and public utilities. It allowed selecting dominant threats localization which is the basis of development of economically feasible solutions to strengthen financial and economic security of companies.